The Effect of Organizational Bullying on Emotional Exhaustion Mediating by Psychological Distress (Case Study: Shariati Hospital Nurses in Tehran) - Abbasali Rastgar; Mahdieh Vishlaghi (Tehran University of Medical Sciences, 2021)
Objective: Organizational bullying leads to uncontrollable stressful situations in which people cannot perform their tasks properly and relax and this may lead to fatigue and exhaustion. The aim of this study is to determine the effect of organizational bullying on emotional exhaustion mediated by nurses' psychological distress. Methodology: This study is applied research and descriptive. The population of the study is the nurses of Shariati Hospital in Tehran. 148 questionnaires returned Based on simple random sampling and the research data analyzed using SPSS and AMOS software. Research variables measured using the questionnaire of organizational bullying of Inerson et al. (2009), psychological distress of Kessler et al. (2003) and emotional Exhaustion of Maslaj and Jackson (1981). Results: Organizational bullying has effect on nurses' emotional Exhaustion directly and also effect on nurses' emotional Exhaustion through mediation of psychological distress indirectly. Conclusion: The results of the present study have brought innovations in the field of organizational bullying and psychological distress of nurses and also help hospital managers to understand the effect of organizational bullying on nurses' emotional Exhaustion by providing comfortable working conditions to prevent emotional Exhaustion. Also because of the effect of organizational bullying on psychological distress, managers have to create a friendly atmosphere to prevent such psychological states so that they can provide appropriate services.